The use of phosphorylated insulin-like growth factor binding protein-1, the Actim Partus test to predict preterm birth in asymptomatic high-risk women. (16th November 2010) - Khambay, H; Bolt, L; Chandiramani, M; De Greeff, A; Shennan, A
Abstract : Objective: The Actim Partus test has been shown to be a useful predictor of preterm birth in symptomatic women but it has not been assessed in high-risk asymptomatic women. This is the first study to evaluate the use of this test in this population and to compare it to the fetal fibronectin (fFN) test. Study Design: All asymptomatic high-risk women attending a Preterm Surveillance Clinic at St Thomas' Hospital, London over a 9-month period had an Actim Partus and fFN test undertaken. Results: 69 patients were eligible. The positive predictive value (PPV) and negative predictive value (NPV) of the Actim Partus test for delivery at ≤37 weeks' gestation for tests undertaken at 19+0–20+6 weeks' gestation were 60% and 39%. Women presenting at 23+0–24+6 week's had both Actim Partus and fFN tests undertaken. The PPV and NPV for the Actim Partus test were 0% and 70%, respectively. The PPV and NPV of fFN test was 67% and 79%, respectively. Conclusion: The Actim Partus test did not perform well as a predictor of preterm birth in high-risk asymptomatic population prior to 24 weeks gestation in this small study. fFN prediction was similar to previous studies. Actim Partus maybe most valuable in symptomatic women.